Opposite effects of visual and auditory word-likeness on activity in the visual word form area - Ludersdorfer, Philipp; Schurz, Matthias; Richlan, Fabio; Kronbichler, Martin; Wimmer, Heinz (Frontiers in Human Neuroscience, 2013)
The present fMRI study investigated the effects of word-likeness of visual and auditory stimuli on activity along the ventral visual stream. In the context of a one-back task, we presented visual and auditory words, pseudowords, and artificial stimuli (i.e., false-fonts and reversed-speech, respectively). Main findings were regionally specific effects of word-likeness on activation in a left ventral occipitotemporal region corresponding to the classic localization of the Visual Word Form Area (VWFA). Specifically, we found an inverse word-likeness effect for the visual stimuli in the form of decreased activation for words compared to pseudowords which, in turn, elicited decreased activation compared to the artificial stimuli. For the auditory stimuli, we found positive word-likeness effects as both words and pseudowords elicited more activation than the artificial stimuli. This resulted from a marked deactivation in response to the artificial stimuli and no such deactivation for words and pseudowords. We suggest that the opposite effects of visual and auditory word-likeness on VWFA activation can be explained by assuming the involvement of visual orthographic memory representations. For the visual stimuli, these representations reduce the coding effort as a function of word-likeness. This results in highest activation to the artificial stimuli and least activation to words for which corresponding representations exist. The positive auditory word-likeness effects may result from activation of orthographic information associated with the auditory words and pseudowords. The view that the VWFA has a primarily visual function is supported by our findings of high activation to the visual artificial stimuli (which have no phonological or semantic associations) and deactivation to the auditory artificial stimuli. According to the phenomenon of cross-modal sensory suppression such deactivations during demanding auditory processing are expected in visual regions.